Управління інтегрованою інформаційною системою на основі моделі колективної поведінки автоматів - Красюк, А. Р. (ХНУРЕ, 2012)
The report is about the approach to the management of an integrated information system with the assumption of disturbance in the structure of location data bases. Proposed using many literals from specified alphabet to represent data. Determined properties of the execution of transaction and disturbance of the integrity of data semantics. Reviewed opportunity of using the behavior theory of automata in stationary medium for providing functioning of integrated information system.
Keywords: інтегрована інформаційна система; локальна інформаційна система